High‐intensity focused ultrasound applied to the placenta using a toroidal transducer: a preliminary ex‐vivo study. (3rd March 2015) - Caloone, J.; Huissoud, C.; Vincenot, J.; Kocot, A.; Dehay, C.; Chapelon, J. Y.; Rudigoz, R. C.; Melodelima, D.
Abstract : Linked Comment: Ultrasound Obstet Gynecol 2015; 45: 247–248 Abstract: Objective: To demonstrate in an ex‐vivo model the feasibility of applying high‐intensity focused ultrasound (HIFU) using a toroidal transducer for the creation of placental lesions. Methods: In this study we used a toroidal transducer, composed of 32 ring‐shaped emitters with an ultrasound probe at the center, operating at a frequency of 2.5 MHz. We examined 45 human placentae, following either normal vaginal delivery or medical termination of pregnancy between 17 and 40 gestational weeks. First, the attenuation coefficients of 12 human placentae were measured and integrated into a numerical model for simulating HIFU lesions. Then, using acoustic parameters from this preliminary study, we performed ex‐vivo experiments with 33 human placentae, each overlain with an animal abdominal wall to simulate the maternal wall. We created single HIFU lesions in 25 of these placentae, and a series of six juxtaposed lesions in eight, studying these both sonographically and macroscopically. Results: Human placental attenuation coefficients of the 12 human placentae ranged from 0.072 to 0.098 Np/cm/MHz, according to gestational age. The 25 single HIFU lesions created had an average diameter of 7.1 ± 3.2 mm and an average depth of 8.2 ± 3.1 mm. The average diameter of the eight series of six juxtaposed HIFU lesions was 23.0 ± 5.0 mm and the average depth was 11.0 ± 4.7 mm. The average thickness of the abdominal walls was 10.5 ± 1.8 mm. No lesions or damage were observed in intervening tissues. Conclusion: This study demonstrates, using an ex‐vivo model, the feasibility, reproducibility, harmlessness and effectiveness of HIFU applied to the human placenta. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.